Comparison Between an Automated and Manual Extraction for the Determination of Immunosuppressive Drugs Whole Blood Concentrations by Liquid Chromatography Tandem Mass Spectrometry. Issue 6 (18th April 2016) - Deslandes, Guillaume; Grégoire, Matthieu; Renaud, Christian; Monteil‐Ganière, Catherine; Azoulay, Claudine; Pineau, Alain; Jolliet, Pascale; Dailly, Eric
Abstract : Background: The whole blood extraction for liquid chromatography tandem mass spectrometry (LC‐MS/MS) of simultaneous quantification of cyclosporine A (Cys A), tacrolimus (Tacrs), sirolimus (Siros), and everolimus (Evers) is still performed manually in many laboratories. The analytical results obtained with an automated method using a liquid handler versus a classical manual preparation were compared. Methods: Cys A ( n = 36), Tacrs ( n = 50), Siros ( n = 34), Evers ( n = 38) whole blood samples of patients were analyzed by LC‐MS/MS assay after manual preparation and automated process using a liquid handling platform including a centrifugation step. Results: The comparison between manual and automated extraction investigated by a linear regression showed a high correlation between results [(Tacrs "automated") = 1.0927 × (Tacrs "manual") − 0.36; (Cys A "automated") = 1.0284 × (Cys A "manual") + 0.0312; (Siros "automated") = 0.9923 × (Siros "manual") + 0.4001; (Evers "automated") = 1.0000 × (Evers "manual") − 0.0600]. Conclusion: The results obtained by the automated and manual preparation are consistent. The automated method is applied for high‐throughput therapeutic drug monitoring of immunosuppressive drugs in routine practice, leading to an increase in quality.